2014
DOI: 10.1523/jneurosci.2582-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Lymphocyte Trafficking with FTY720 Prevents Inflammation-Sensitized Hypoxic–Ischemic Brain Injury in Newborns

Abstract: Intrauterine infection (chorioamnionitis) aggravates neonatal hypoxic-ischemic (HI) brain injury

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 56 publications
2
63
2
Order By: Relevance
“…Notably, the exogenous TLR4 agonist, lipopolysaccharide (LPS), was the most potent stimulus for antigen-loaded macrophages to drive T H 17 polarization in human autologous co-cultures (50). Although T-lymphocytes do not routinely cross the blood-brain barrier (BBB) (51), intraperitoneal LPS administration increased the differentiation and brain influx of T H 17 cells after neonatal hypoxia-ischemia (52). T H 17 cells also comprised a larger proportion of total T-lymphocytes within the brain, as compared to blood; suggesting T H 17 cells may locally polarize and/or preferentially traffic into the CNS after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the exogenous TLR4 agonist, lipopolysaccharide (LPS), was the most potent stimulus for antigen-loaded macrophages to drive T H 17 polarization in human autologous co-cultures (50). Although T-lymphocytes do not routinely cross the blood-brain barrier (BBB) (51), intraperitoneal LPS administration increased the differentiation and brain influx of T H 17 cells after neonatal hypoxia-ischemia (52). T H 17 cells also comprised a larger proportion of total T-lymphocytes within the brain, as compared to blood; suggesting T H 17 cells may locally polarize and/or preferentially traffic into the CNS after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…While the efficacy of T H 1/T H 17 inhibition remains unexplored after TBI, T H 17 cells drove chronic microglial polarization after EAE and co-culture studies showed myelin-specific T-lymphocytes that secreted IL-17 potently activated inflammatory cytokine expression in microglia [268, 269]. Furthermore, attenuation of brain T H 17 influx reduced white matter injury, limited brain atrophy, and prevented chronic functional deficits after neonatal hypoxia-ischemic injury [270]. These findings are in line with reports showing myelin-reactive T H 17 cells induced demyelination and impaired endogenous remyelination in pre-clinical white matter injury models and in multiple sclerosis patients [271276].…”
Section: Translational Implicationsmentioning
confidence: 99%
“…Similarly, the TLR4 agonist, LPS, induced IL-23 expression in peritoneal macrophages via TLR4 activation [286]. Finally, HMGB1-TLR4 signaling also increased myeloid IL-23 expression and subsequent T H 17 production/mobilization after myocardial ischemia-reperfusion [287], periodontitis [288], or neonatal hypoxia-ischemia [270], although this issues remains to be fully studied after TBI. Given the temporal delay between TBI and adaptive immune responses, blocking T H polarization, secondary to DAMP-induced macrophage activation, may provide a feasible approach to limit long-term progressive injury.…”
Section: Translational Implicationsmentioning
confidence: 99%
“…In a model of hypoxia/ischemia with systemic inflammation (lipopolysaccharide; to mimic intrauterine infection) in rats, Yang et al [135] found an early (4 h) infiltration of T-lymphocytes (CD43+) into the CP. This was blocked by fingolimod (FTY720; a sphingosine-1-phosphate receptor modulator) treatment which also markedly reduced the brain injury in lipopolysaccharide-enhanced hypoxia/ischemia injury.…”
Section: Choroid Plexus As a Responder To Injurymentioning
confidence: 99%